Incidence of musculoskeletal disorders among newly employed manufacturing workers - Häkkänen, Marketta; Viikari-Juntura, Eira; Martikainen, Rami (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'The incidence of upper-limb, neck-shoulder, and low-back disorders and their induction times were investigated among new workers in tasks with various physical workloads. ' ' METHODS ': 'New trailer assemblers (N=364) were followed prospectively for 45 months - the workers` health status via medical records and exposure to physical workload factors via job titles, walk-throughs, task descriptions, and some direct measurements. The incidence rate of first sick leave due to such disorders was calculated for different workload groups. The proportion of workers surviving without musculoskeletal disorders was estimated by the Kaplan-Maier product-limit estimator, and the effect of the exposure on the risk of incident disorders was estimated with the Cox proportional hazards model. ' ' RESULTS ': 'The highest annual incidences were observed for strenuous tasks, the incidence rate for men being 16.8 per 100 person-years [95% confidence interval (95% CI) 8.0-30.9] for upper-limb disorders in strenuous tasks and 6.1 (95% CI 2.0-14.1) in nonstrenuous tasks and that for women being 32.0 (95% CI 11.7-69.7) and 9.9 (95% CI 0.2-54.9), respectively. The men`s risk of contracting an upper-limb or neck-shoulder disorder in strenuous tasks was about threefold [hazard ratio (HR) 3.2 (95% CI 1.1-9.4) for upper-limb disorders and 2.7 (95% CI 0.9-8.1) for neck-shoulder disorders] that of nonstrenuous tasks, whereas workload seemed not to affect low-back disorders. The workers first sought medical advice for their disorders typically some months after employment began. ' ' CONCLUSIONS ': 'Newly employed workers in hand-intensive tasks have a high risk of upper-limb and neck-shoulder disorders. An etiologic role for activities involving high force demands in upper-limb and neck-shoulder disorders is possible.
Keywords: assembly work; induction time; low back; manufacturing worker; MSD; musculoskeletal disorder; neck; physical workload; shoulder; sick leave; survival; upper limb